Identification of Food Expenditure and Food Security of Muslim Households: Evidence from Indonesian Family Life Survey 2007 and 2014 - Setiawati, Nadya; Putri, Ananda Sintia; Setiawan, Agung (Department of Islamic Economics, IPB University, 2024)
This study examines the impact of religiosity on household food consumption and food security in Indonesia, particularly among Muslim households. Despite the acknowledgment of religious factors in food-related policies, limited research has explored their specific influence on food expenditure and security. Using longitudinal data from the Indonesian Family Life Survey (IFLS) covering 2007 and 2014, this study analyzes food expenditure and food security levels among Muslim households, employing the Propensity Score Matching (PSM) model. The analysis includes variables such as age, education, marital status, employment, and gender. Findings reveal that religiosity negatively influences food expenditure, both in total and per capita, suggesting that religious households tend to spend less on food. Moreover, Muslim households demonstrate higher levels of food security, often reporting moderate or adequate food security, compared to non-religious households. This indicates a potential protective effect of religiosity on food stability. The study recommends integrating financial education programs that emphasize frugality and mindful consumption. Additionally, strengthening community-based support systems, such as zakat and sadaqah, could play a crucial role in improving food assistance and security.